The Beneficial effects of alternative methods, with an emphasis on yoga, for patients affected by pain associated with endometriosis - Kutyła, Katarzyna; Marszałek, Anna; Choiński, Maciej; Wasiewicz-Ciach, Paulina; Marzec, Marcelina Teresa; Kuczyński, Piotr; Wydra-Rojek, Aleksandra; Łakoma, Aleksandra; Marzec, Weronika Zofia; Mokot, Wojciech Jan (Quality in Sport, 2024)
Aim of the study The aim of this systematic review is to compare studies published since 2017 to evaluate whether yoga and other alternative methods should be recommended to patients with endometriosis and associated pain. As alternative methods, particularly yoga, have gained popularity in recent years, it is crucial for healthcare professionals to ensure that these approaches are scientifically valid. This systematic review examines the effects of practicing different types of yoga and possible advantages of other alternative methods that could be potentially beneficial on pain management for patients suffering form endometriosis. Methods This review synthesizes findings from twenty studies, including randomized controlled trials and observational studies. Conclusion The results consistently indicate significant improvements in the quality of life for patients with endometriosis. Yoga, as both a physical and mental practice, appears to be beneficial in managing pain. Although there are some limitations related to study design and variability, the evidence strongly supports the benefits of yoga in managing pelvic pain. Future research should focus on identifying which specific types of yoga practices offer the greatest benefits.